Impact of a Mindfulness-Based Intervention on Basic Psychological Need Satisfaction and Internalized Symptoms in Elementary School Students With Severe Learning Disabilities: Results From a Randomized Cluster Trial - Malboeuf-Hurtubise, Catherine; Taylor, Geneviève; Mageau, Geneviève A. (Frontiers in Psychology, 2019)
Background Mindfulness is hypothesized to lead to more realistic appraisals of the three basic psychological needs, which leads people to benefit from high levels of need satisfaction or helps them make the appropriate changes to improve need satisfaction. Mindfulness-based interventions (MBIs) have also shown promise to foster greater basic psychological need satisfaction in students with learning disabilities (LDs). Objective The goal of the present study was to evaluate the impact of a MBI on the satisfaction of the basic psychological needs and on internalized symptoms in students with severe LDs. A randomized cluster trial was implemented to compare the progression of need satisfaction, anxiety, and depression symptoms in participants pre- to post-intervention and at follow-up. Method Elementary school students with severe LDs (N = 23) in two special education classrooms took part in this study and were randomly attributed to either an experimental or an active control group. Results Mixed ANOVAs first showed that the experimental condition did not moderate change over time such that similar effects were observed in the experimental and active control groups. Looking at main effects of time on participants’ scores of autonomy, competence, and relatedness across time, we found a significant within-person effect for the competence need (p = 0.02). Post hoc analyses showed that for both groups, competence scores were significantly higher at post-intervention (p = 0.03) and at follow-up (p = 0.04), when compared to pre-intervention scores. A significant main effect was also found for anxiety levels over time (p = 0.008). Post hoc analyses showed that for both groups, scores were significantly lower at post-intervention (p = 0.01) and at follow-up (p = 0.006), when compared to pre-intervention scores. Conclusion Although the MBI seemed useful in increasing the basic psychological need of competence and decreasing anxiety symptoms in students with severe LDs, it was not more useful than the active control intervention that was used in this project. Future studies should verify that MBIs have an added value compared to other types of interventions that can be more easily implemented in school-based settings.